15N-urea metabolism in the functioning human colon: luminal hydrolysis and mucosal permeability. Issue 4 (April 1990) - Moran, B J; Jackson, A A
Abstract : The biopsy channel of the colonoscope was used in a novel approach to the study of in vivo colonic nitrogen metabolism in 12 subjects. A tracer dose of 15N15N-urea was placed in the caecum in six and distal to the splenic flexure in six. The urine and stool were collected for 72 hours and isotopic enrichment was measured in a mass spectrometer. A similar proportion of the dose was recovered in the urine as 15N15N-urea from the right colon, 6%, as was recovered from the left, 4%, showing that the urea was absorbed intact. Urinary 15N14N-urea from the right colon was 18% of the dose compared to 13% from the left colon. This represents urea that has been hydrolysed and absorbed as ammonia. Less than 4% of the dose was recovered in the stool. The greatest proportion of the label, 74% from the right and 82% from the left, could not be accounted for in the urine or the stool and is presumed to have entered the metabolic pool of nitrogen. We conclude that; the colon is permeable to urea, intraluminal hydrolysis occurs and that urea nitrogen enters the metabolic pool of nitrogen in functionally significant quantities.